The Potency of Collecting Larvae of Oryctes rhinoceros L. (Coleoptera:Scarabaeidae) in the Oil Palm Plantation - Anugerah Pustakawan Pradipta; F. X. Wagiman; Witjaksono Witjaksono (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
The intensive and continuous collection of rhinoceros beetles, Oryctes rhinoceros L. (Coleoptera: Scarabaeidae), is an extraordinary strategy in IPM (Integrated Pest Management). This study was intended to evaluate the potency of people in collecting larvae and to determine the age structure of the beetle population. The study was conducted in Asahan Regency, North Sumatera Province. Adult men, adult women, adolescent girls, and adolescent boys collected beetles for 2 hours in each breeding site. Results showed that the beetle was more significant abundant in decomposed trunks at plots of immature and mature palms than at heaps of the empty fruit bunches namely 236, 221 and 93 individuals/2 hours. The population age-structure showed significantly predominant of 2nd and 3rd instars in all breeding sites, i.e. eggs, 1st instars, 2nd instars, and 3rd instars, pupae, adult males, and adult females were 2.02, 23.29, 21.39, 47.06, 3.17, 0.86, and 2.21%, respectively. Adult men, adult women, and adolescent boys had similar potency in collecting 3rd instar larvae while the least amount was collected by the adolescent girls viz. 70, 85, 60, and 38 larvae/2 hours, respectively. It is suggested that the study results support future efforts in the sustainable control of rhinoceros beetle through collecting larvae for commercial utilization.